Human resource practices: training initiatives and development of the employees a study on The ACME Laboratories Limited - Liana, Nasiha Alam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.